2021
DOI: 10.3390/ijms22095006
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects Cardiac Tissue in Experimental Malignant Hypertension Due to Antioxidant, Anti-Inflammatory, and Anti-Apoptotic Properties

Abstract: Hypertension is one of the most prevalent and powerful contributors of cardiovascular diseases. Malignant hypertension is a relatively rare but extremely severe form of hypertension accompanied with heart, brain, and renal impairment. Resveratrol, a recently described grape-derived, polyphenolic antioxidant molecule, has been proposed as an effective agent in the prevention of cardiovascular diseases. This study was designed to examine chronic resveratrol administration on blood pressure, oxidative stress, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…Previous studies verified that RESV suppresses NF κ B activation and gene expression along with the expression of proinflammatory cytokines [ 35 ]. According to Grujic Milanovic et al, RESV intake protected the cardiomyocytes through the inhibition of MPO activity, suggesting its promising anti-inflammatory and cardioprotective properties [ 36 ]. A remarkable finding from Yan et al discussed that RESV improved cardiovascular function by decreasing circulating levels of proinflammatory cytokines such as of tumor necrosis factor- α (TNF- α ) or interleukin-6 (IL-6) and by suppressing nuclear factor kappa B (NF- κ B) pathway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies verified that RESV suppresses NF κ B activation and gene expression along with the expression of proinflammatory cytokines [ 35 ]. According to Grujic Milanovic et al, RESV intake protected the cardiomyocytes through the inhibition of MPO activity, suggesting its promising anti-inflammatory and cardioprotective properties [ 36 ]. A remarkable finding from Yan et al discussed that RESV improved cardiovascular function by decreasing circulating levels of proinflammatory cytokines such as of tumor necrosis factor- α (TNF- α ) or interleukin-6 (IL-6) and by suppressing nuclear factor kappa B (NF- κ B) pathway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a nonflavonoid polyphenolic compound found in grapes, Thuja, peanuts, and many other plants, mediating anti-inflammatory effects and inhibiting the function of cyclooxygenase and hydroperoxidase, is widely used in research on cardiovascular protection [ 33 ]. Epidemiological research has proven that resveratrol can prevent various diseases, including atherosclerosis and other cardiovascular diseases [ 34 ]. Resveratrol exerts some physiological functions in VSMCs, including inhibition of high glucose-induced migration mediated by focal adhesion kinase and attenuation of homocysteine-mediated cell proliferation [ 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro and in vivo studies also showed that GP possesses antioxidant activity useful in the management of the prooxidant status, considered a key factor in atherosclerosis development. Thus, GP can increase SOD, CAT, GPx, and/or GRx levels [ 79 , 80 , 81 , 82 ] and reduce ROS GSH, TBARS, and/or superoxide levels [ 83 , 84 , 85 ] being useful in primary prophylaxis.…”
Section: In Vitro and In Vivo Studies—grape Pomace Antioxidant And An...mentioning
confidence: 99%